Templated polymers enable selective capture and release of lysophosphatidic acid in human plasma via optimization of non-covalent binding to functional monomers. Issue 22 (12th October 2015) - Wang, Jialu; Sibrian-Vazquez, Martha; Escobedo, Jorge O.; Wang, Lei; Chu, Yu-Hsuan; Moore, Richard G.; Strongin, Robert M.
Abstract : Isolation of lysophosphatidic acid from human plasma is accomplished by selective solid-phase extraction materials that function through templation and supramolecular interactions. Abstract : The first solid phase extraction materials for selective lysophosphatidic acid (LPA) enrichment from human plasma are described. Molecularly imprinted polymers were designed, synthesized and evaluated as cartridge fillings. They enabled a relatively rapid and simple extraction protocol for LPA without any need for multiple liquid–liquid extraction steps. The five major subspecies of lysophosphatidic acid are readily separated from all other native plasma phospholipids, including those well-known to interfere with LPA quantitation, such as phosphatidylcholine and lysophosphatidylcholine. Outstanding LPA purity is obtained via these solid phase materials in a tandem extraction setup.